Genetic and metabolomic analysis of AdeD and AdeI mutants of de novo purine biosynthesis: cellular models of de novo purine biosynthesis deficiency disorders - Duval, Nathan; Luhrs, Kyleen; Wilkinson, Terry G; Baresova, Veronika; Skopova, Vaclava; Kmoch, Stanislav; Vacano, Guido N; Zikanova, Marie; Patterson, David (Molecular genetics and metabolism, 2013)
Purines are molecules essential for many cell processes, including RNA and DNA synthesis, regulation of enzyme activity, protein synthesis and function, energy metabolism and transfer, essential coenzyme function, and cell signaling. Purines are produced via the de novo purine biosynthesis pathway. Mutations in purine biosynthetic genes, for example phosphoribosylaminoimidazole carboxylase/phosphoribosylaminoimidazole succinocarboxamide synthetase (PAICS, E.C. 6.3.2.6/E.C. 4.1.1.21), can lead to developmental anomalies in lower vertebrates. Alterations in PAICS expression in humans have been associated with various types of cancer. Mutations in adenylosuccinate lyase (ADSL, E.C. 4.3.2.2) or 5-aminoimidazole-4-carboxamide ribonucleotide formyltransferase/IMP cyclohydrolase (ATIC, E.C. 2.1.2.3/E.C. 3.5.4.10) lead to inborn errors of metabolism with a range of clinical symptoms, including developmental delay, severe neurological symptoms, and autistic features. The pathogenetic mechanism is unknown for these conditions, and no effective treatments exist. The study of cells carrying mutations in the various de novo purine biosynthesis pathway genes provides one approach to analysis of purine disorders. Here we report the characterization of AdeD Chinese hamster ovary (CHO) cells, which carry genetic mutations encoding p.E177K and p.W363* variants of PAICS. Both mutations impact PAICS structure and completely abolish its biosynthesis. Additionally, we describe a sensitive and rapid analytical method for detection of purine de novo biosynthesis intermediates based on high performance liquid chromatography with electrochemical detection. Using this technique we detected accumulation of AIR in AdeD cells. In AdeI cells, mutant for the ADSL gene, we detected accumulation of SAICAR and SAMP and, somewhat unexpectedly, accumulation of AIR. This method has great potential for metabolite profiling of de novo purine biosynthesis pathway mutants, identification of novel genetic defects of purine metabolism in humans, and elucidating the regulation of this critical metabolic pathway.
Keywords: Purines; Purine-Pyrimidine Metabolism, Inborn Errors; sekvence nukleotidů; mutace; karboxylyasy; Carboxy-Lyases; Metabolomics; Peptide Synthases; vysokoúčinná kapalinová chromatografie; metabolomika; CHO Cells; molekulární sekvence - údaje; puriny; sekvenční seřazení; Models, Biological; Electrochemical Techniques; Chromatography, High Pressure Liquid; molekulární modely; elektrochemické techniky; Cricetulus; Models, Molecular; Cricetinae; Animals; CHO buňky; biologické modely; zvířata; Molecular Sequence Data; Base Sequence; Mutation; poruchy metabolismu purinů a pyrimidinů; křečci praví; peptidsynthasy; Sequence Alignment